SCIENTIFIC BASIS OF CROP CROPPING, SWITCHING TO ROTATION AND ADJUSTING IT - Raxmanov Ergash Asadullayevich, To’rayeva Zuxra Muxtorovna, Namozov Sanjar Mamanazarovich, Xujanazarova Munavvar Rustamovna (Galaxy International Interdisciplinary Research Journal, 2023)
Crop rotation is the most important part of the farming system. It is an effective measure to ensure soil fertility and increase crop productivity. This article contains information about the scientific theoretical basis of crop rotation and the necessary recommendations for switching to crop rotation and its mastery.